Bell's palsy with abnormal findings in the ipsilateral parotid gland. Issue 1 (31st December 2023) - Hijioka, Takaaki; Aoki, Yoshihiro; Moteki, Hideaki; Mizushiro, Naoto
Abstract: Bell's palsy (BP) can be caused by acute or chronic inflammation-related demyelination. We describe a pediatric case of BP in which a concomitant ipsilateral parotid gland anomaly of unknown etiology was observed. A 7-year-old boy was admitted to the hospital with a 5-day history of left facial paralysis and swelling of ipsilateral parotid gland. Ultrasonography revealed hypoechoic masses, and T2-weighted magnetic resonance imaging revealed heterogeneous hyperintensity in the left parotid gland. After treatment with prednisolone combined with valacyclovir, the facial paralysis improved; however, the abnormal imaging findings in the left parotid gland remained unchanged five months after the onset. Further investigations were not performed because the patient was completely asymptomatic. Hence, the association between BP and parotid gland lesions was not determined in this case, which warrants further investigation in future research to elucidate the association in relevant cases.